PERLINDUNGAN KONSUMEN ATAS PENERAPAN KLAUSULA EKSONERASI DALAM PERJANJIAN KEANGGOTAAN FIT HUB MENURUT UNDANG-UNDANG NOMOR 8 TAHUN 1999: Consumer Protection Against Exclusion Clauses in Fit Hub Membership Agreements Based on Law No. 8/1999 - Muhammad Fathan Zahran Dika; Anna Maria Tri Anggraini (Reformasi Hukum Trisakti, 2024)
Economic transactions, such as buying and selling goods or services, often place consumers at a disadvantage due to an unequal position compared to business actors. An example is the FIT HUB membership agreement, which contains an exoneration clause. This study examines the form and content of such clauses under Law No. 8 of 1999 and the legal protection available to consumers. Using normative legal research based on secondary data, the study result and concludes that while the FIT HUB membership agreement does not violate Article 18 paragraph (2) of the Consumer Protection Law—since it is easy for consumers to read—it is invalid under the Civil Code. The agreement fails to meet the objective requirements of Articles 1320, 1337, and 1338. Article 18 paragraph (1) of the Consumer Protection Law prohibits exoneration clauses, with legal consequences being that such clauses are null and void, as stipulated in Article 18 paragraph (3). Legal protection for consumers can be preventive, through sectoral regulations and the Consumer Protection Law, or repressive, through civil and criminal sanctions.